Polymer Scaffolds-Enhanced Bone Regeneration in Osteonecrosis Therapy - Dong, Hengliang; Zhu, Tongtong; Zhang, Mingran; Wang, Dapeng; Wang, Xukai; Huang, Guanning; Wang, Shuaishuai; Zhang, Minglei (Frontiers in Bioengineering and Biotechnology, 2021)
Osteonecrosis without effective early treatment eventually leads to the collapse of the articular surface and causes arthritis. For the early stages of osteonecrosis, core decompression combined with bone grafting, is a procedure worthy of attention and clinical trial. And the study of bone graft substitutes has become a hot topic in the area of osteonecrosis research. In recent years, polymers have received more attention than other materials due to their excellent performance. However, because of the harsh microenvironment in osteonecrosis, pure polymers may not meet the stringent requirements of osteonecrosis research. The combined application of polymers and various other substances makes up for the shortcomings of polymers, and to meet a broad range of requirements for application in osteonecrosis therapy. This review focuses on various applying polymers in osteonecrosis therapy, then discusses the development of biofunctionalized composite polymers based on the polymers combined with different bioactive substances. At the end, we discuss their prospects for translation to clinical practice.